Fast but transient recovery of aquatic and terrestrial communities after a large dam removal - Dézerald, Olivier; Roussel, Jean-Marc; Lanoë, Elven; Beauverger, Thibaut; Bazin, Alan; Rodríguez-Pérez, Héctor; Dufour, Simon; Bernez, Ivan; Piscart, Christophe (Frontiers in Ecology and Evolution, 2023)
Ecological restoration through dam removals receives increasing attention from scientists, environmental managers and policy makers. However, most dam removal projects focus on small structures (< 10 m in height) and on few ecosystem compartments at a time (e.g. river morphology, reservoir sedimentation, aquatic invertebrates, terrestrial vegetation), but rarely aquatic and riparian ecosystems simultaneously. We explored the joint taxonomic recovery (temporal patterns in α-and β-diversity) of three communities after the removal of the Vezins dam (36 m in height; Sélune River, France): aquatic benthic invertebrates, riparian invertebrates, and the riparian vegetation. These communities were monitored yearly, during three years after the dam removal, on sites located within (n = 3; restored sites) and outside (n = 3; two upstream and one downstream; non-impounded sites) the former reservoir. Results showed a fast recovery of the three ecological communities, as patterns in α-diversity between restored and non-impounded sites were not necessarily different from each other 1.5 years after complete reservoir dewatering. The mean number of species or morphospecies (± standard deviation) reached up to 28.2 ± 5.2, 17.0 ± 2.3 and 77.5 ± 11.2 for the aquatic invertebrates, and the riparian vegetation and invertebrates, respectively. Relative to the sampled area, the riparian invertebrates were the most diversified of all ecological communities with > 500 taxa (i.e., pooling all sites and years). In addition, in some restored sites, α-diversity kept increasing over time while species turnover (β-diversity) remained high after three years for all ecological communities suggesting a transient recovery (i.e., still facing temporal changes in species diversity and composition). This recovery was mediated by the identity of the ecological community as inter-annual changes in α-and β-diversity of the riparian vegetation were less pronounced compared to those of aquatic and terrestrial invertebrates. This recovery depended also on site-specific features as the most distant restored site from the former dam had more time for recovery following the slow reservoir dewatering and through increased sedimentation in the downstream site. Differential patterns of recovery in α-and β-diversity found in this study are discussed in light of species functional traits and ecosystem functioning.